2014
DOI: 10.1111/j.2047-2927.2014.00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment by testicular sperm extraction and intracytoplasmic sperm injection of 65 azoospermic patients with non‐mosaic Klinefelter syndrome with birth of 17 healthy children

Abstract: SUMMARYThe aim of this work was to present the clinical and embryological outcomes of 65 azoospermic patients with non-mosaic Klinefelter syndrome (KS), treated by testicular sperm extraction (TESE), followed by intracytoplasmic sperm injection (ICSI), either with fresh or cryopreserved testicular spermatozoa. In total, spermatozoa were recovered in 25/65 (38.5%) of the cases. Of the 48 patients who choose to perform TESE followed by ICSI using fresh testicular spermatozoa (treatment TESE), spermatozoa was rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
51
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 86 publications
5
51
1
3
Order By: Relevance
“…Nowadays, the fertility therapy available for azoospermic KS men is based on TESE (Testicular Sperm Extraction after Biopsy) and assisted reproduction12. The molecular networks involved in KS spermatogenic and testicular failure could represent the basis for the identification of new therapy targets and the set-up of early treatments preserving residual fertility.…”
mentioning
confidence: 99%
“…Nowadays, the fertility therapy available for azoospermic KS men is based on TESE (Testicular Sperm Extraction after Biopsy) and assisted reproduction12. The molecular networks involved in KS spermatogenic and testicular failure could represent the basis for the identification of new therapy targets and the set-up of early treatments preserving residual fertility.…”
mentioning
confidence: 99%
“…ICSI provides the only sufficient treatment to overcome severe forms of male infertility using the primary spermatocyte, round spermatid, elongating spermatid, elongated spermatid, or spermatozoa stages (Hourvitz et al, 1998;Kahraman et al, 1999;Balaban et al, 2001;Madureira et al, 2014). However, male infertility is linked to several genetic problems such as an increased number of chromosomal aberrations, cystic fibrosis transmembrane conductance regulator gene mutations, Y chromosome microdeletions, and androgen receptor mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The fluorescence in situ hybridization (FISH) technique is a very important tool for cancer cytogenetic studies, genetic gene mapping, and chromosome disease diagnosis at the DNA level (Fu et al, 1996;Yung, 1996). Since intracytoplasmic sperm injection (ICSI) was first reported in 1992 (Palermo et al, 1992), numerous cases of the highly successful use of ICSI have been reported (Balaban et al, 2001;Ludwig et al, 2001;Madureira et al, 2014). ICSI has become the treatment of choice for male factor infertility.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature shows the micro-TESE SRR to be between 38-63% in NOA patients [6][7][8][9] . Given the SRR results from this study particularly in men with normal range FSH ≤ 10IU/L, we found that TESA in our experience had similar results compared to micro-TESE.…”
Section: Discussionmentioning
confidence: 99%